A brief history of the thermal properties metrology. (April 2020) - Hay, Bruno
Highlights: Metrology appeared in concomitant way with the establishment of commercial exchanges. Birth of thermal properties metrology coincides with appearance of temperature scales. First measurement methods of thermal properties were developed in the 18th century. A major advance was to perform energy calibrations by electrical substitution. National metrology institutes started to study thermal properties end of 19th century. Abstract: The metrology of thermal properties, which is more recent than that of length and mass, coincides with the creation of thermometers and the implementation of the temperature scales. The first major contributions to the study of thermal properties can be attributed to Franklin who devised in 1780 an experiment to evaluate the relative capacities of thermal conduction of different materials, and to Lavoisier who developed in 1782 an ice calorimeter for the relative measurements of specific and latent heat. It was not until 1807 that the first determination of an absolute value of thermal conductivity was done by Fourier. The experimental discovery of Joule around 1860, concerning the relationship between the heat generated and current flowing through a conductor, was the next important contribution to the development of metrology of thermal properties, as it provided for the first time the possibility of producing a known amount of heat by electrical way. The instruments involving generation or measurement of heat fluxes could be thus calibrated by Joule effect, enabling to improve the traceability to the International System of Units (SI) of thermal properties measurements. This principle was applied by the National Metrology Institutes, which have worked on the measurement of thermal properties from the beginning of the 20th century by developing reference facilities based on the implementation of "absolute" methods. This paper retraces the major developments in the metrology of thermal properties from its beginnings until now.